Topochemical fluorination of some Ruddlesden-Popper phases - Zhang, R (2017)
This thesis describes the synthesis and the characterization of some n = 2 Ruddlesden-Popper oxide phases (A3B2O7; A = La, Y, Sr or Ca; B = Cr, Ni or Mn) and their topochemically fluorinated phases. La2SrCr2O7 adopts an A2/a (a-a-c-/a-a-c-) distorted structure with antiferromagnetic order below TN ~ 260 K. DFT calculations performed on La2SrCr2O7 suggest that this highly distorted A2/a (a-a-c-/a-a-c-) structure is stabilized by energy gains from the charge equalization and the improvement of chromium bonding environments associated with the unusual Sr/La distribution exhibited by this phase (the 12-coordinate A-sites are occupied by 82(2)% La3+ and 18(2)% Sr2+). Topochemical fluorination of La2SrCr2O7 (Cr3+) yields La2SrCr2O7F2 (Cr4+) adopting the A2/a (a-a-c-/a-a-c-) distortion with antiferromagnetic order below TN ~ 140 K. The fluorination leads a great compression of the perovskite layer within the Ruddlesden-Popper structure, enhancing the (a-a-c-/a-a-c-) distortion. As a result La2SrCr2O7F2 lies further from the crossover for insulating to metallic behaviour than many other Cr4+ oxide phases. The A-site doping in La2SrCr2O7 for the preparation of La2-xSr1+xCr2O7 (x = 0.2, 0.3) and La2Sr0.5Ca0.5Cr2O7 leads to no obvious change in structural framework and the antiferromagnetic behaviour. La2-xSr1+xCr2O7F2 (x = 0.2, 0.3) behaves similarly to La2SrCr2O7F2. Topochemical fluorination of La3Ni2O7 yields La3Ni2O5.5F3.5 with no obvious magnetic order. The fluorination leads to an enhancement of the structural distortion exhibited by the oxide starting material, driving a change from an Amam, a-a-c0/a-a-c0 lattice distortion to a Pnam a-a-c+/a-a-(c+) lattice distortion in the fluorinated phase. The introduction of a cooperative octahedral tilt around the crystallographic z-axis leads to a local breaking of the inversion symmetry of the host lattice on fluorination, although the global inversion symmetry of the lattice is retained due to an alternation in the z-tilt direction in adjacent perovskite sheets. The substitution of Sr2+ with Ca2+ cations in YSr2Mn2O7 led to an increasing distortion of the metal-oxide framework, resulting in the formation of an orthorhombic symmetry in space group Pnnm adopted by YSr0.5Ca1.5Mn2O7. This novel Pnnm (a-b-c0/b-a-c0, a ≠ b) distortion can be seen as an intermediate in structural change from P42/mnm (a-b0c0/b0a-c0) to Amam (a-a-c0/a-a-c0). The topochemical fluorination of YSr2Mn2O7 yields YSr2Mn2O5.5F3.5 with P42/mnm (a-b0c0/b0a-c0) distortion. The fluorination YSr2Mn2O7 does not lead to a structural change as observed in that of La3Ni2O7. This preference of retaining relatively high symmetry is driven by the A-cation ordering over the 9- and 12-coordinate A-sites in YSr2Mn2O5.5F3.5.